Downregulation of SUMO2 inhibits hepatocellular carcinoma cell proliferation, migration and invasion. Issue 6 (14th May 2021) - Chen, Jintu; Chen, Canwei; Lin, Yongfa; Su, Yongfa; Yu, Xueping; Jiang, Yancheng; Chen, Zixuan; Ke, ShaoYing; Lin, ShaoZe; Chen, LiangJuan; Zhang, Zhishan; Zhang, Tao
Abstract : This study aimed to evaluate the prognostic value and biological function of small ubiquitin‐like modifier 2 ( SUMO2 ) in hepatocellular carcinoma (HCC). SUMO2 expression in HCC tissues was markedly higher than that in normal liver tissues, and patients with high SUMO2 expression had significantly shorter median overall survival than those with low SUMO2 expression. Furthermore, SUMO2 expression was closely correlated with lymph node metastasis and vascular invasion and was a predictor of poor prognosis. The knockdown of SUMO2 in two HCC cell lines (SMMC‐7721 and Bel‐7404) dramatically suppressed their proliferation, migration and invasion. Western blot analysis showed that the downregulation of SUMO2 significantly reduced the expression of Ki‐67, matrix metalloproteinase‐9 (MMP‐9) and vascular endothelial growth factor (VEGF) in SMMC‐7721 and Bel‐7404 cells. Similarly, quantitative reverse transcription–PCR revealed consistently decreased expression of MMP‐9 and VEGF . Our data suggest that SUMO2 promotes proliferation, migration and invasion of HCC cells via mechanisms involving MMP‐9 and VEGF. Therefore, SUMO2 may be a prognostic factor and a promising therapeutic target for patients with HCC. Abstract : We observed that the overexpression of small ubiquitin‐like modifier 2 ( SUMO2 ) in hepatocellular carcinoma (HCC) tissues is associated with poor prognosis in patients with HCC. Silencing of SUMO2 in HCC cell lines reduced the expression of both vascular endothelial growth factor (VEGF) and matrix metalloproteinase‐9 (MMP‐9). SUMO2 promoted the tumorigenic phenotypes of HCC cells through mechanisms involving MMP‐9 and VEGF. Therefore, SUMO2 may serve as a prognostic marker and a promising therapeutic target for patients with HCC.